A Modified Shapley Value Model for Equitable Benefit Distribution in Design-Led EPC Consortia - Jiangtao Lao; Zhongfu Qin (Buildings)
The Engineering, Procurement, and Construction (EPC) model—particularly the design-led consortium structure—has proven effective in enhancing design quality, improving construction feasibility, and reducing project costs. Nonetheless, its broader application remains constrained by difficulties in quantifying consortium members’ future benefits and establishing an equitable benefit distribution mechanism. These issues often undermine cooperation and limit the scalability of the model. To address these challenges, this study proposes a benefit distribution model that incorporates two quantifiable indicators of members’ future benefits: the bid-winning rate and the profit margin of future projects. The model further enhances fairness by modifying the classical Shapley value method. It introduces a cost compensation factor and a benefit entitlement influence factor to account for differences in both resource input and initial contractual entitlements. Results from a case study of a national highway reconstruction project in Hangzhou, China, demonstrate that the proposed model produces distribution outcomes more closely aligned with actual contractual benchmarks and improves fairness and acceptance among consortium members.